Controlled gastrointestinal digestion of micellar casein loaded anthocyanins: The chelating and complexing effect of dextran sulfate. (November 2022) - Liao, Minjie; Chen, Fang; Hu, Xiaosong; Liao, Xiaojun; Miao, Song; Ma, Lingjun; Ji, Junfu
Abstract: Casein micelle is known to be a CCP-mediated tight structure that often shows unique stomach curd behavior and rapid intestinal hydrolysis. These inherent properties make it difficult for casein micelles-formed powders called micellar casein (MC) to achieve high loading capacity and controlled release of loaded bioactive compounds. In this study, dextran sulfate (DS) was used as a calcium chelator to combine with MC, and spray-dried microparticles were prepared to load blueberry anthocyanins (ACNs). In vitro gastrointestinal digestion was carried out to investigate the relationship between the structural changes of MC induced by DS as well as the dynamic release process of ACNs. The results indicated that the encapsulation efficiency of microparticles increased from 52.76% ± 2.36%–91.86% ± 0.87% with the addition of DS. During in vitro digestion, the different CCP dissociation degrees induced by DS resulted in different dissolution and curdling abilities of microparticles in the stomach, which thus precisely controlled the release process of ACNs. Simultaneously, the combination with DS could delay the disintegration of the structures of microparticles in the small intestine, thereby hindering the degradation of ACNs. This study will contribute to the design of casein-based delivery systems and the development of related functional products. Graphical abstract: Image 1 Highlights: MC formed curds in the stomach and hydrolyzed quickly in the small intestine. The digestion properties made MC fail to achieve controlled release of ACNs. DS with calcium chelating ability could adjust the digestion properties of MC. The less release of ACNs was achieved by the structure barrier of DS.